Four new species of Sathytes Westwood (Coleoptera: Staphylinidae: Pselaphinae) from the island of Borneo - Shen, Qi; Yin, Zi-Wei (Zootaxa, 2019)
The pselaphine genus Sathytes Westwood is represented in Borneo by a single species. In this paper we describe four new species: S. borneoensis sp. nov., S. liuyei sp. nov., S. larifuga sp. nov., and S. shihongliangi sp. nov. All new species were collected by light traps in Sabah, and show unique combinations of male sexual characters that lead to ready species discriminations. A key to Sathytes species from Borneo is appended.